NOTE ON HYMENODICTYON (RUB.) AND ITS OCCURRENCE IN MALESIA, ESPECIALLY IN WEST JAVA - STEENIS, C. G. G. J. VAN (Research Center for Biology, 1972)
The genus Hymenodictyon is a genus of often large, often deciduous trees which is widely distributed over the African and Asian-Malesian tropics, with 11 species recorded for Madagascar.